Influence of a Hydrostatical High-Pressure on Plasticity of Solids - Kozak, L.; Kozak, O. (Physics and Chemistry of Solid State, 2015)
On the two-dimensional model of the crystal it was shown that the crystal lattice transform from stable to unstable under the influence of hydrostatical high pressure. As a result of such transformation is intensity the processes of plastic deformation. It is known that all of solid bodies become plasticity and electric conductivity under the influence of a hydrostatical high-pressure. The reason of it is additional displacement of atoms of a crystal lattice. A high plasticity and electric conductivity of metals occurs due to additional displacement of atoms also. This displacement takes a place due to the specific of the interatomic interaction.